The diagenetic continuum of steroid hydrocarbon transformation from early diagenesis into the oil window. (1st February 2023) - Synnott, Dane P.; Schwark, Lorenz; Dewing, Keith; Percy, Emma L.; Pedersen, Per Kent
Abstract: Steroids and their derivatives are ubiquitous in the sedimentary rock record, where they are widely applied as biological or geochemical markers to determine organic facies as well as thermal maturation of bitumen and oils covering the diagenetic to catagenetic stages. The diagenetic continuum from early diagenesis into catagenesis of steroids has not been extensively studied despite the importance of these reactions in influencing the successive continuum of late diagenetic transformations. This study utilizes a stratigraphically constrained transect of 9 wells from the Upper Cretaceous Second White Specks and Belle Fourche formations of south-central Alberta, Canada ranging in thermal maturity from 0.2 %VRE to 0.8 %VRE. Biomarkers were examined from 69 samples from 8 wells and thermal maturity was determined from 87 samples from 9 wells using HAWK programmed pyrolysis analysis. Relative and absolute abundances of regular sterane, diasterene, diasterane, monoaromatic steroid, and triaromatic steroid biomarkers and changes in the proportions of steroid compound classes were determined and evaluated for thermal maturity. Additionally, isomerization ratios within each of the compound classes were examined with increasing thermal maturation. Rearranged diasterenes initially dominate the steroidal hydrocarbons, followed by diasteranes in the late diagenetic and catagenetic stages and at peak oil maturity (0.8 %VRE) diasteranes were most abundant. The relative abundance of a steroid is initially controlled by its rate of production or isomerization from a biological precursor, but at higher thermal maturities selective catagenetic destruction alters the relative abundance of steroid classes, with aromatic steroids and regular steranes being degraded or expelled earliest. Thermal maturity parameters based on the isomerization of regular steranes, and the aromatization of monoaromatic steroids are effective thermal maturity indicators in specific but overlapping ranges beginning at 0.2 %VRE. This work represents a novel examination of a natural thermal maturity transect and helps to consolidate our understanding and application of the diagenetic transformations of steroid compounds.